2022
DOI: 10.3390/cells11030364
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Arginine Methyltransferases in Neuromuscular Function and Diseases

Abstract: Neuromuscular diseases (NMDs) are characterized by progressive loss of muscle mass and strength that leads to impaired body movement. It not only severely diminishes the quality of life of the patients, but also subjects them to increased risk of secondary medical conditions such as fall-induced injuries and various chronic diseases. However, no effective treatment is currently available to prevent or reverse the disease progression. Protein arginine methyltransferases (PRMTs) are emerging as a potential thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 125 publications
1
7
0
Order By: Relevance
“…The expression of these genes was not measured in this study; however, it is likely that this increased methylation alters their expression and therefore the specification, differentiation and/or maturation of the MNs. Other studies (Sanchez et al, 2013; Lee et al, 2022) have shown dysregulations in the abundance of several methyltransferases in SMA, that we have also detected in a MS study on HB9-purified MNs that we have performed (unpublished). Epigenetic modifications in SMA patients, SMN-dependent or independent, could be reason for the different disease phenotypes that patients carrying the same SMN2 copy number present and for the variable response of SMA patients to treatments.…”
Section: Discussionsupporting
confidence: 78%
“…The expression of these genes was not measured in this study; however, it is likely that this increased methylation alters their expression and therefore the specification, differentiation and/or maturation of the MNs. Other studies (Sanchez et al, 2013; Lee et al, 2022) have shown dysregulations in the abundance of several methyltransferases in SMA, that we have also detected in a MS study on HB9-purified MNs that we have performed (unpublished). Epigenetic modifications in SMA patients, SMN-dependent or independent, could be reason for the different disease phenotypes that patients carrying the same SMN2 copy number present and for the variable response of SMA patients to treatments.…”
Section: Discussionsupporting
confidence: 78%
“…Among 3 types of protein arginine methyltransferases (Prmts), Prmt1 belongs to the type I Prmt and catalyzes asymmetric arginine dimethylation of histone and nonhistone substrates thereby modulating signaling pathways and gene expression related to diverse cellular events [ 15 , 19 ]. While Prmt1 knockout mice die early during embryogenesis [ 20 ], recent studies using mice lacking Prmt1 in muscle stem cells or myofibers have revealed essential roles of Prmt1 in muscle regeneration and maintenance [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, a total of nine members of the PRMT family in the human body have been discovered, and according to the different methylation products, they can be divided into three types: type I PRMTs (PRMT1, 2, 3, 4, 6, and 8) catalyze the production of MMA and ADMA; type II PRMTs (PRMT5 and 9) catalyze the production of MMA and SDMA ( Dominici et al, 2021 ); type III PRMT (PRMT7) only catalyze the production of MMA ( Zurita-Lopez et al, 2012 ). Among them, PRMT1 is the most abundant and responsible for 90% of arginine methylation in mammalian cells ( Lee et al, 2022 ). To date, enhanced PRMT1 expression has been well documented in a variety of cancers, including lung cancer, and is correlated with a poor prognosis of tumor development through its promotion on tumor cell growth, proliferation, invasion, and metastasis ( Wang et al, 20211004 ; Wang et al, 2021 ; Yao et al, 2021 ; Yin et al, 2021 ; Hua et al, 2020 ; Repenning et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%